Rhetorical code studies discovering arguments in and around code - Brock, Kevin (Digital rhetoric collaborative., 2019)
"In Rhetorical Code Studies, Kevin Brock explores how software code serves as a means of meaningful communication through which amateur and professional software developers construct arguments--arguments that are not only made up of logical procedures but also of implicit and explicit claims about how a given program works (or should work). These claims appear as procedures and as conventional discourse in the form of code comments and in email messages, forum posts, and other venues for conversation with other developers. To investigate the rhetorical qualities of code, Brock extends ongoing conversations in rhetoric and composition on software by turning to a number of case examples ranging from large, well-known projects like Mozilla Firefox to small-scale programs like the "FizzBuzz" test common in many programming job interviews. These examples, which involve specific examination of code texts as well as the contexts surrounding their composition, demonstrate the variety and depth of rhetorical activity taking place in and around code, from individual differences in style to changes in large-scale community norms"--